Nilai-Nilai Perjuangan Dalam Novel Dompet Ayah Sepatu Ibu Karya J.S Khairen - Anita Prima Putri; Hayati, Yenni (Universitas Negeri Padang, 2024)
This research aims to describe: (1) the form of the value of being willing to sacrifice in the novel Dad's Wallet Mom's Shoes by J.S Khairen, (2) the manifestation of the value of unity in the novel Dad's Wallet Mom's Shoes by J.S Khairen, (3) the manifestation of the value of respect in the novel Dad's Wallet Mom's Shoes J.S Khairen's work, (4) the value of spirit and never giving up exists in the novel Dad's Wallet Mom's Shoes J.S khairen's work, (5) there is a value of cooperation in the novel Dad's Wallet Mom's Shoes by J.S Khairen. This type of research is literary research using descriptive methods. The data source used is a novel Dad's Wallet Mom's Shoes by J.S Khairen. Based on the research results, three forms of the value of being willing to sacrifice, two forms of the value of unity, two forms of the value of respect, five forms of enthusiasm and never giving up, and three forms of the value of cooperation were found in the novel Dad’s Wallet Mom’s Shoes by J.S Khairen.